The song of significance a new manifesto for teams - Godin, Seth. (New York Portfolio, 2023)
From the bestselling author of Linchpin and Tribes comes a new challenge to leaders of all stripes The workplace has undergone a massive shift. Remote work and economic instability have depressed innovation and left us disconnected and disengaged. Paychecks no longer buy loyalty, happiness, and effort. Quiet quitting runs rampant, and people show up without truly showing up. Alarmed managers are doubling down on keystroke surveillance, productivity tracking and back-to-the-office mandates, when what they should be doing is the opposite - affording employees the dignity necessary to inject purpose and motivation into their work. In The Song of Significance, legendary author and business thinker Seth Godin posits a new view of what industry leaders must do now. The choice is simple: either keep treating your people as disposable and join in the AI-fueled race to the bottom, or build a significant organization that enrolls, empowers, and trusts employees to deliver their best work, no matter where they're working from. If you want your employees to turn their cameras on, participate in conversations, and live up to their full professional potential, you must give them the respect and autonomy they deserve as humans. Godin offers a series of commitments leaders must make, and a list of organizational milestones on the way to significance. It's time for leaders to make and keep a new promise, and to recognize that, as Godin says, "Humans aren't a resource. They are the point."
Keywords: Leadership